Persepsi Remaja Mengenai Nasehat Reproduksi Pada Saat Mengalami Menarche di Garut - esa Risi Suazini (STIKes Karsa Husada Garut, 2019)
Teenagers are susceptible to falling into promiscuity. The impact of promiscuity is contracting Sexually Transmitted Diseases (STDs). Greater impact can be experienced by adolescents who have experienced menarche, other than contracting STDs can also unwanted pregnancy, abortion and young pregnancy. Adolescents need guidance in dealing with life, based on data from the Ministry of Health in 2015, amounting to 14% or about 6 million adolescents to have free sex. Adolescent reproductive health problems can continue to reproductive health problems in adulthood. The purpose of this study was to determine the perceptions of young women regarding reproductive advice when she experienced menarche in Garut. This research is useful as a reference for parents to pay more attention to adolescents and as input to the government in developing new strategies in increasing knowledge, forming adolescent attitudes and behavior in reproductive health. The research method used is the mix method by means of a later interview survey to get a generalization of the phenomenon from the perception of the respondent (grounded theory).The results of the study obtained answers that the majority of respondents did not get optimal reproductive advice, mothers as the main people who provide reproductive advice and advice that adolescents get when experiencing menarche are general interaction, attention to worship, cleanliness, types of food and drinks and advice in the form of myths or cultures that develop in the community